Coffin-Lowry syndrome: clinical and molecular features. Issue 10 (1st October 2002) - Hanauer, A; Young, I D
Abstract : The Coffin-Lowry syndrome (CLS) is a rare X linked disorder in which affected males show severe mental retardation with characteristic dysmorphism, most notably affecting the face and hands. The typical facial features consist of a prominent forehead, hypertelorism, a flat nasal bridge, downward sloping palpebral fissures, and a wide mouth with full lips. Mild progression in facial coarsening occurs during childhood and adult life. The hands are broad with soft, stubby, tapering fingers. Other clinical findings include short stature (95%), a pectus deformity (80%), a kyphosis and/or scoliosis (80%), mitral valve dysfunction, and sensorineural hearing loss. The causal gene, RSK2, was identified in 1996 and contains 22 exons which encode a protein of 740 amino acids. Over 75 distinct pathogenic mutations have been identified in 250 unrelated CLS patients.